Contribution of Grass Component (Ground Storey) in Afforested Areas in Arid Regions - Ahuja, L. D.; Sharma, S. K.; Verma, C. M.; Lamba, T. R. (Indian Forester, 1985)
Production of grass in areas afforested with Prosopis cineraria, Albizzla lebbak, Tecomella undulata and Acacia senegal in arid conditions of Jodhpur for five years (1972-76) was evaluated. Total forage production under the species averaged to 1.494, 1.352, 1.413 and 0.634 t/ha respectlvely, when population of respective tree species was 566.6, 283.3, 383.3 and 1516.6 per hectare. Contribution of perennial species was highest (74.77%) under Prosopis cineraria and least under Tecomella undulata (53.72%) and Acacia senegal(52.5%). Forage production was influenced by total precipitation and also its pattern of distribution; maximum being during 1973 and least being during 1974 and 1972. Perennial species contributed highest during the years when precipitation was low and/or ill distributed, indicating drought hardy nature of perennial grass species.